View of the Berkeley Building from the corner of Arlington and Boylston Streets, ca. 1953 - Barnes, Kenneth C. (Tufts Archival Research Center, 2005)
Street-level view southwest, from the corner of Arlington and Boylston Streets, of the Berkeley Building, located at 200 Berkeley Street. A weather beacon is located on top of the building's roof. The Arlington Street Church, located at the corner of Arlington and Boylston Streets, is darkened by a shadow along the right side of the photograph. Signage adorns the facades of several buildings lining Boylston Street that are included in the photograph. Designed by Cram and Ferguson, 1947. Donated by Robert Severy. 7 5/8 x 9 1/2, 7 7/8 x 9 15/16 overall Photographs